The Massachusetts colony - Fradin, Dennis B. (Chicago : Childrens Press, 1987)
A history of the colony, which began with the settling of the Pilgrims in Plymouth, until its becoming the sixth state of the Union. Includes brief biographies of notable colonial-era people.
Includes index.
Keywords: Massachusetts -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature; Massachusetts -- History -- Revolution, 1775-1783 -- Juvenile literature; Massachusetts -- History -- Colonial period, ca. 1600-1775.; Massachusetts -- History -- Revolution, 1775-1783.